Why I am a pluralist - Weyl, E. Glen (RadicalxChange, 2022)
I increasingly use the terms “pluralist” to describe myself and “Plurality” to describe the direction I want to see technology go in.[1] This essay, following up on my “Why I am not" series [2], tries to articulate what I mean by this and where it might lead us. The piece filters through my academic-technologist lens many things I have learned since Eric Posner and I published Radical Markets, but more than anything what I have learned from my fellow RadicalxChange board members Danielle Allen, Audrey Tang and Christopher Kulendran Thomas.[3] While the piece raises many more questions than it answers, my hope is that these will be precise enough, in a way they have not been in the past, to help stimulate a coherent Plurality agenda for technology.